The incidence of posttreatment pain using two different intracanal medicaments (Mustansiria Dental Journal, 2018)
The purpose of this study was to compare the incidence of posttreatment pain to two medicaments placed in the root canal system. One hundred teeth belonging to 100 patients were included in this study. All teeth under went conventional root canal, which involved the instrumentation to the apices of each canal at the first visit. Canals were instrumented using a step-back technique and hand-files along with irrigant. The canals were dried and one of the following two medicaments was inserted into the canal: group I: Chlorhexidine- containing gutta-percha point; group II Calcium hydroxide- containing gutta-percha point. All teeth were temporized with intermediate restorative material. Patients' assessed posttreatment pain up to 48 hours as none, mild, moderate, or sever. The pain levels in each test group at each time period were compared statistically with Chi-square test, a significant difference was found in posttreatment pain between the two groups at 4h and 24h. No significant difference in posttreatment at 48h.